(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
This paper explores the dynamic definition of types in the context of algorithm science, highlighting its implications for programming language design, software engineering, and data representation. By analyzing theoretical and practical perspectives, we aim to predict future trends in type systems and their applications.